2022
DOI: 10.1177/00222194211065498
|View full text |Cite
|
Sign up to set email alerts
|

A Synthesis of the Conceptualization and Measurement of Implementation Fidelity in Mathematics Intervention Research

Abstract: In intervention studies, high rates of implementation fidelity are important markers of a study’s success; however, the definition of implementation fidelity is both complex and dynamic. In this synthesis, we examined the dimensions of implementation fidelity measured and reported in 99 studies in which researchers utilized a mathematics intervention for elementary students (i.e., Grades 1–5). We examined implementation fidelity following recommendations made by Dane and Schneider; O’Donnell; and DeFouw et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 126 publications
0
12
0
Order By: Relevance
“…However, reviews of implemented educational interventions have demonstrated that interventionist-controlled factors (especially adherence) are more commonly reported than measures of participant responsiveness ( O’Donnell, 2008 ). When responsiveness is considered, dosage is the most often-reported measure ( Bos et al, 2022 ). Measurement of active participant engagement in early childhood interventions has primarily been concentrated on the adult participants who implement the intervention with children (e.g., teachers and parents’ active participation with the intervention).…”
Section: Introductionmentioning
confidence: 99%
“…However, reviews of implemented educational interventions have demonstrated that interventionist-controlled factors (especially adherence) are more commonly reported than measures of participant responsiveness ( O’Donnell, 2008 ). When responsiveness is considered, dosage is the most often-reported measure ( Bos et al, 2022 ). Measurement of active participant engagement in early childhood interventions has primarily been concentrated on the adult participants who implement the intervention with children (e.g., teachers and parents’ active participation with the intervention).…”
Section: Introductionmentioning
confidence: 99%
“…Intervention is a complex system (Bos et al., 2022), and investigating the domains of implementation that support or hinder student achievement within this system is imperative to improve student achievement. Implementation includes a myriad domains and underlying factors (Bos et al., 2022; O'Donnell, 2008) that are often discussed and measured differently across research groups (Harn et al., 2013).…”
Section: Promising Mathematics Interventionsmentioning
confidence: 99%
“…Intervention is a complex system (Bos et al., 2022), and investigating the domains of implementation that support or hinder student achievement within this system is imperative to improve student achievement. Implementation includes a myriad domains and underlying factors (Bos et al., 2022; O'Donnell, 2008) that are often discussed and measured differently across research groups (Harn et al., 2013). Though researchers may report on these aspects of implementation (Bos et al., 2022; Jitendra et al., 2021), few have evaluated the relation between intervention implementation and student outcomes (Capin et al., 2018; O'Donnell, 2008).…”
Section: Promising Mathematics Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fidelity of implementation, particularly curriculum implementation, can be viewed as rigid adherence to the full curriculum as written, or a loose adherence to the intention or spirit of the curriculum with room for flexibility, or somewhere in between. The field of education research lacks consensus of which aspects of fidelity are most critical to report or how to measure them, thus translating those expectations to teacher implementers remains ambiguous (Bos et al, 2022;Dane, 1998;Defouw et al, 2019). In a seminal review of fidelity as a concept, it was noted that fidelity and adherence were frequently defined in the same or similar ways but that as curricula moves from conception to…”
Section: Evidence-based Curriculum and Fidelitymentioning
confidence: 99%